Effects of cardiac rehabilitation on cardiac autonomic functions in ankylosing spondylitis patients: A randomized controlled study (Annals of Medical Research, 2021)
Aim: Ankylosing spondylitis (AS) is a systemic chronic inflammatory disease that has various adverse effects on cardiac autonomicfunctions. On the other hand, there is no data regarding the effects of cardiac rehabilitation on cardiac autonomic functions in ASpatients. In this study, we aimed to investigate the effects of cardiac rehabilitation on cardiac autonomic nervous system parametersin patients with AS.Materials and Methods: This study was designed as a prospective randomized controlled trial. The study was carried out in December2015 - August 2016. 34 patients who fulfilled the modified New York criteria were enrolled in the study. Patients were randomlyassigned into case and control groups each consisting of 17 patients. The cardiac rehabilitation program was applied to the casegroup for eight weeks. Patient evaluation with clinical assessment, echocardiography, and exercise stress testing was performedbefore and after treatment.Results: A total of 34 patients made the final study population (37.35± 5.22 years, 55.9% male). There were no significant differencesregarding the baseline characteristics between case and control groups. Patients in the case group had better MET levels, exercisetime, resting heart rate, and chronotropic reserve than the control patients following cardiac rehabilitation.Conclusion: Our results indicate that significant improvement in cardiac autonomic functions can be obtained in AS patients whenthe cardiac rehabilitation program is combined with the medical treatment.